Two-dimensional and three-dimensional ultrasonographic diagnosis of congenital auricular anomalies - Wang, Huanyu; Lv, Ke; Wu, Xining; Zhang, Yixiu; Ouyang, Yunshu; Lv, Yan; Jiang, Yulin; Fan, Yue; Chen, Xiaowei; Meng, Hua (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the role of prenatal ultrasound and three-dimensional ultrasound in the diagnosis of fetal congenital auricular malformations.MethodsThe ultrasonographic features of 14 fetuses diagnosed with auricular malformations at Peking Union Medical College Hospital between May 2019 and May 2024 were retrospectively reviewed, and pregnancy outcomes were followed up.ResultsThe median gestational age at which congenital auricle deformities were detected by ultrasound was 24 weeks 5 days. Of the 14 cases, 5 had bilateral deformities, 5 had right-sided deformities, and 4 had left-sided deformities. The auricular abnormalities detected included microtia, low set ears, accessory auricles, abnormal ear helix and question mark ear, all of which were confirmed by postnatal follow-up or pathological examination after termination. Ten fetuses underwent three-dimensional ultrasound, which provided additional diagnostic details. Eight fetuses presented with other systemic deformities: three had facial deformities such as micrognathia, nasal bone absence, and facial cleft, while five had additional structure anomalies including diaphragmatic hernia, cardiac anomalies, and polydactyly. Genetic testing was performed in nine cases: one fetus had complete trisomy 18, one had Xp22.31 duplication, and seven had normal results. Six pregnancies were electively terminated, while eight fetuses were carried to term. Among the newborns, four had no significant hearing impairment, four others (three with microtia and one with a question mark ear) had hearing loss and required further reconstructive treatment.ConclusionCongenital auricular deformities exhibit characteristic ultrasound features, and in most cases, prenatal diagnosis and evaluation can be achieved through ultrasound. This provides valuable information to support clinical decision-making and prenatal counseling.